The gradient is $m=-4/3$, and the point given is $(3/2,3)$

Let $c$ be the $y$-intercept

$y=mx+c$

$y=(-4/3)x+c$

If I substitute $x$ and $y$ from the point given, $3=(-4/3)(3/2)+c$ and look for $c$, I get $c=5$

But according to my answer sheet, $c=33/8$ by using $y-{y}_{1}=m(x-{x}_{1})$

Why are the two methods giving different answers?

Let $c$ be the $y$-intercept

$y=mx+c$

$y=(-4/3)x+c$

If I substitute $x$ and $y$ from the point given, $3=(-4/3)(3/2)+c$ and look for $c$, I get $c=5$

But according to my answer sheet, $c=33/8$ by using $y-{y}_{1}=m(x-{x}_{1})$

Why are the two methods giving different answers?